Animal Rights and Protection against Cruelty in Ukraine - YATSENKO, Ivan V.; ZAPARA, Svitlana I.; ZON, Gregory A.; IVANOVSKAYA, Lydmyla B.; KLOCHKO, Alyona M. (Journal of Environmental Management and Tourism, 2020)
The article deals with the issues of the animal rights protection in Ukraine. Views of the prominent scientists are examined and the provisions of the current international and Ukrainian legislation are analyzed to establish the lacks in the legislative regulations of the animals protection from the cruel treatment. It is noted that an animal is a creature, but not a thing as it is prescribed by the civil legislation in Ukraine. Some particular terms, such as “bullying”, concerning the cruel treatment with animals are analyzed. The interpretation of the concept of "cruel methods" in the scientific and reference literature is studied. Сonclusionsare made, that animal abuse is a socially dangerous, unlawful, guilty, punishable, intentional action, provisioned by the Criminal legislation and according to the animal's health consequences, animal abuse may cause: non-lethal damage or death. In this regard Ukrainian legislation needs to be amended essentially,